Lack of Difference in Treatment Patterns and Clinical Outcomes Between Black and White Patients With Inflammatory Bowel Disease. Issue 12 (18th May 2018) - Barnes, Edward L; Kochar, Bharati; Long, Millie D; Pekow, Joel; Ananthakrishnan, Ashwin; Anyane-Yeboa, Adjoa; Martin, Christopher; Galanko, Joseph; Herfarth, Hans H; Kappelman, Michael D; Sandler, Robert S
Abstract: Background: Previous reports have shown differences in phenotypes among black patients with inflammatory bowel disease (IBD) compared with other racial groups, but prior studies were limited by small numbers of black patients and cross-sectional analyses. We used data from the Sinai-Helmsley Alliance for Research Excellence cohort to compare phenotypes and treatment patterns of black and white patients with IBD in a prospective study. Methods: We compared phenotypes, IBD-specific therapies, and health care utilization among black and white patients with IBD. For all analyses, we performed bivariate analyses and multivariable logistic regression to adjust for potential confounders. Results: Among 5537 patients with IBD, 314 (6%) reported black race. Black patients were more likely to report a Crohn's disease (CD)–related complication at baseline (adjusted odds ratio [aOR], 1.44; 95% confidence interval [CI], 1.06–1.95). Black patients with CD were more likely to develop a new abscess (aOR, 2.27; 95% CI, 1.31–3.93) and initiate an anti–tumor necrosis factor therapy during follow-up (aOR, 1.85; 95% CI, 1.09–3.14). Black patients with ulcerative colitis were more likely to have proctitis (24% vs 13%, P = 0.033) at baseline. There were no differences in surgery or hospitalization rates during the follow-up period. Conclusions: Black patients with CD demonstrated increased complications at baseline and during follow-up in this cohort. Despite more complicated disease, black and white patients with IBD were generally given the same medications and experienced similar rates of hospitalization and surgery during the study period. In our multicenter cohort, clinical outcomes among black and white patients with IBD were similar.